The intellectual and political foundations of the effective and ineffective state: the international and political journal - faten mohammed razak ا. م. د فاتن محمد (The International and Political Journal, 2025)
The state is considered one of the most important political forms and actors in our world today. Its presence is still essential in contemporary political processes. Despite the changes that have afflicted states and transformed them from a modern state to a post-modern state, its role and existence still reflects its form today according to contemporary names: (the effective and ineffective failed state,soft, weak...) Its role in performing its function and its policy followed in resolving political and non-political crises reflects not only its strength, effectiveness, and continued existence, but also its non-transformation into a failed or fragile state... which varies from one state to another according to internal variables and the influence of the international environment on it. The difference between countries is not the availability of government or authority, but rather the ability to act and implement it.